Help-Seeking Behaviors in Research Data Management - Jeremy Kenyon; Ramirose Attebury; Jylisa Doney; Marco Seiferle-Valencia; Jessica Martinez; Bruce Godfrey (Issues in Science and Technology Librarianship, 2021)
Investigations on the help-seeking behavior of academic library patrons have to date primarily focused on the undergraduate experience, most often in the context of reference interactions. This study seeks to explore the help-seeking behaviors of a different audience - faculty in the natural and physical sciences at an R2 land-grant university. Eighteen faculty in the natural and physical sciences at the University of Idaho were individually interviewed using an in-depth qualitative interview format and all transcripts were coded and analyzed using an open transcript data visualization tool created at the University of Idaho Library.